Perception of tourism management students towards the implementation of blended learning for the new academic year - Initan, Jezarish J.; Initan, Vinice Joyce T.; Montecillo, Lovely Joy G. (Digos City : UMDC, 2023)
The COVID-19 pandemic in the Philippines forced educational sectors to transition to virtual and modular learning for safety and public safety. However, schools resumed face-to-face classes, introducing blended learning modalities. This quantitative study of 233 tourism management students aimed to explore the perception of tourism management students regarding implementing blended learning for the new academic year and its impact on them. The data was analyzed using the mean, Mann-Whitney U-test, and Kruskal Wallis Test. Findings showed that the overall mean perception of tourism management students regarding implementing blended learning was high, which means that students had a high perception of face-to-face and online learning. No significant differences were found on the students' perceptions of blended learning in terms of sex and age, however, the fourth year students had the highest satisfaction on the learning modality among the year levels. Future studies that compare face-to-face and online modalities of the tourism degree at UM Digos College are recommended.
Includes references and appendices.
Keywords: Tourism Management -- Undergraduate thesis